2013
DOI: 10.1016/j.bbrc.2013.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cytoprotective autophagy in PC-12 cells by cadmium

Abstract: Laboratory data have demonstrated that cadmium (Cd) may induce neuronal apoptosis. However, little is known about the role of autophagy in neurons. In this study, cell viability decreased in a dose- and time-dependent manner after treatment with Cd in PC-12 cells. As cells were exposed to Cd, the levels of LC3-II proteins became elevated, specific punctate distribution of endogenous LC3-II increased, and numerous autophagosomes appeared, which suggest that Cd induced a high level of autophagy. In the late stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 35 publications
6
28
1
Order By: Relevance
“…So the function of autophagy in Cd-exposed cells can differ. Wang reported that cytoprotective autophagy could be induced by 20 μmol/L Cd at 4 h in neural cells [42]. In this study, we used biochemical assays to confirm that autophagy was activated during the process of Cd-induced cortical neuron injury, and we found that autophagy played a cytoprotective role during cadmium-induced oxidative damage in primary neurons.…”
Section: Discussionsupporting
confidence: 50%
“…So the function of autophagy in Cd-exposed cells can differ. Wang reported that cytoprotective autophagy could be induced by 20 μmol/L Cd at 4 h in neural cells [42]. In this study, we used biochemical assays to confirm that autophagy was activated during the process of Cd-induced cortical neuron injury, and we found that autophagy played a cytoprotective role during cadmium-induced oxidative damage in primary neurons.…”
Section: Discussionsupporting
confidence: 50%
“…Therefore, measuring the level of LC3 II alone does not determine whether autophagy is induced or inhibited. Wang et al [27] showed that treatments of PC-12 cells with autophagy inhibitor chloroquine and autophagy inducer rapamycin can both increase LC3 II levels. The p62 protein, also called poly-ubiquitin binding protein sequestosome 1, is another marker of macroautophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies report that low-level cadmium exposure can cause cell autophagy in several types of cells such as PC12 cells, MES-13 mesangial cells, skin epidermal cells, and vascular endothelial cells [27,[34][35][36]. Low-level cadmium inhibits apoptosis by serum and basic fibroblast growth factor (bFGF) deprivation and promotes autophagy [35].…”
Section: Mechanisms Of Ca 2+ Homeostasis-mediated Cell Autophagy Indumentioning
confidence: 99%